Physical Handicap as a Reason for Divorce: Case Study at the Sharia Court, Banda Aceh, Indonesia - Makinara, Ihdi Karim; Ungel, Jamhuri; Arrazi, Fitrah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
In the city of Banda Aceh, Indonesia, divorce is permissible in some circumstances including physical infirmities, such as when a husband experiences an erectile dysfunction. Under the Islamic law, divorce is permissible and the woman has the right to initiate divorce proceedings and pursue legal action. This study aims to examine the perspectives of judges at the Banda Aceh Syari'iyah Court regarding divorce cases involving individuals with physical disabilities. This study scrutinizes the practical legal methods employed by analyzing them from the perspective of the Islamic family law principles. This article analyzes the practical legal methods employed by studying the perspectives of the Islamic family law. Conversely, the process of collecting data entails scrutinizing documents, such as legal judgments, pertinent literature, and scholarly papers. According to Hanafi and Malikischolars, divorce due to physical inability is classified as talak ba'in, as determined by this study. Conversely, the Shafi'i and Hanbali schools are seen solely as a means to breach the sacrificial pact (fasakh). If this divorce is determined to be valid, the husband will have two opportunities to legally execute the divorce in order to remarry this woman. According to this, the Banda Aceh Sharia Court concluded that a husband's inability to perform sexually might be considered a valid reason for his inability to fulfill his responsibilities. Testimony from witnesses confirmed this, providing evidence that the legal proceedings adhered to Islamic law. Consequently, this study concludes that divorce occurs when a husband's physical impairment hinders his ability to fulfill his obligations, leading to the breakdown of the marriage. However, the Sharia Court provides a remedy (dispensation) to address the medical condition (impotence) so that the judges might take it into account when seeking reconciliation between the two parties, if the condition is resolved.